Factors associated with influenza vaccination uptake among healthcare workers in tertiary hospitals in Perak / Rosidah Omar - Rosidah, Omar (2019)
Influenza is the leading cause of respiratory illness worldwide and has a substantial medical, social and economic impact. Healthcare workers (HCWs) are at high risk of infection and can easily spread the disease. Hence, the influenza vaccination is an important preventive action that can be taken to stop the transmission of this disease. However, the uptake among HCWs remains low, and many HCWs were doubt about the effectiveness of the vaccine. Thus, the factors associated with the uptake and the effectiveness of the influenza vaccination need to be studied to understand the reasons behind the poor uptake. Therefore, the objective of this study is to measure the prevalence of influenza vaccination and to determine the factors associated with influenza vaccination uptake and the effectiveness of the vaccination on influenza-related work absenteeism among HCWs in tertiary hospitals in Perak, Malaysia. The study was conducted in two phases. In Phase 1, knowledge (KQ), behavioural determinants (BDQ) and health literacy (HLQ) questionnaires were piloted among 100 HCWs in a tertiary hospital in Selangor, Malaysia to determine content validity, internal consistency and testretest validity. As a result, the KQ was reduced from 11 to eight items, and the BDQ was reduced from 46 to 40 items. The 14 items in the HLQ were retained. The revised questionnaires had adequate consistency and reliability and were used in Phase 2 of the study. In Phase 2, a cross-sectional study was carried out in two specialist hospitals in Perak. It involved 775 nurses and assistant medical officers who were selected using simple random sampling. The study used a self-administered questionnaire that contained a section on sociodemographic characteristics, the KQ, BDQ, HLQ and the number of influenza-related sick days in 2017. The vaccination uptake was based on the iv immunization records for the period between 1 November 2016 and 31 December 2016. The results revealed that the prevalence of influenza vaccination uptake among HCWs was 25.5%. A multivariate logistic regression showed that the factors associated with influenza vaccination were increasing age (Odds ratio (OR) 1.04; 95% confidence interval (CI) 1.01,1.08; p-value 0.015); working in an emergency department (OR 7.20; 95% CI 1.45,35.69; p-value 0.016) or obstetrics & gynaecology (O&G) department (OR 0.17; 95% CI 0.04,0.85; p-value 0.003) compared to other departments, and working as a community nurse compared to an assistant medical officer (OR 8.48; 95% CI 1.33,54.0; p-value 0.024). With regards to absenteeism, there was no significant difference in the mean number of cumulative sick days per person (p=0.3881). However, the total number of workday lost among non-vaccinated was 1.44 times higher than among the vaccinated group. In conclusion, influenza vaccination coverage was found to be low (25.5%). The above-identified factors and the effectiveness of the vaccination should inform future vaccination campaigns and the development of targeted intervention programmes to increase influenza vaccination uptake.